Effects of benzo(a)pyrene at environmentally relevant doses on embryo-fetal development in rats - da Silva Moreira, Suyane [UNESP]; de Lima Inocêncio, Leonardo Cesar [UNESP]; Jorge, Bárbara Campos [UNESP]; Reis, Ana Carolina Casali [UNESP]; Hisano, Hamilton; Arena, Arielle Cristina [UNESP] (Wiley, 2021)
Studies have demonstrated that Benzo(a)Pyrene (BaP), a polycyclic aromatic hydrocarbon ubiquituous in the environment, can cause teratogenic effects. Since the majority of studies used in vitro models or high doses of BaP, this study evaluated the teratogenicity, reproductive and developmental performance of low doses of BaP through maternal and fetus examination after daily oral administration of BaP (0; 0.1; 1.0 or 10 μg/kg) to pregnant Wistar rats from Gestational day (GD) 6 to GD 15 (the organogenesis period). Pregnant rats did not exhibit clinical signs of toxicity during the exposure period. However, dams exposed to the lowest dose of BaP showed a reduction in the erythrocytes number and in the creatinine levels. The groups exposed to 0.1 and 1.0 μg/kg presented a decrease in placental efficiency, as well as an increase in placental weight. After fetal examination, the treated group with the lowest dose showed a reduced relative anogenital distance, while the curve of normal distribution of weight was changed in the highest dose group. In addition, anomalies evidenced by changes in the renal size and degree of fetal ossification were observed in treated-fetus. In conclusion, treatment with BaP during organogenesis at this dose level is detrimental to the normal development of fetuses.
Keywords: organogenesis; polycyclic aromatic hydrocarbon; rats; skeletal abnormalities; teratogenicity